No longer man, but not yet a woman? Whether or not postoperative transsexuals can seek correction of gender entry in the birth certificate - Lao, Ruby Margaret Tan (Animo Repository, 2005)
This thesis aims to find the answer to the query whether or not postoperative transsexuals can seek correction of gender entry in their birth certificate. This study intends to help the law cope with the continuous changes in scientific and medical advances in technology. The authors of the Civil Code and Family Code were not yet aware that someday it would be possible for a person to change his or her gender through a medical operation. Thus there have been questions of how does the law define a man and a woman. This thesis aims to answer four sub-issues. First, whether or not a person who underwent sex reassignment operation can get married under Philippine laws. Second. whether or not transsexuals who have acquired gender recognition be allowed to have the same rights as those who are biologically female or male. Third, whether or not the Constitutional right to liberty and freedom of expression are broad enough to allow people to choose their own gender. The researchers intend to find the answers by reviewing the provisions of the Family Code, the New Civil Code, the Revised Rules of Court and the 1987 Constitution of the Philippines. The researchers will determine if these laws are still applicable and sufficient to encompass the relationship of homosexuals who underwent sex reassignment operation or there is a need to amend or propose new laws. Interviews with experts such as medical doctors with expertise in obstetrics and gynecology, reconstructive and plastic surgery were conducted. As of now, there are only two cases in the Philippines where a regional trial court granted a petition for change of name and gender of petitioners who underwent sex reassignment operation. The two cases were reviewed. One is still pending in the Court of Appeals and the other was already final and executory for the Solicitor General did not appeal the case. The two cases were used as a primary sources to help answer the main issue. Interviews with these two Judges who rendered the decision were also conducted. Foreign jurisprudence is also used as supplementary basis of arguments.